Synthesis of Modified TiO₂ Nanocomposite using Fe₃O₄ and Nickel as Photocatalyst in Reduction of Silver Ions - Pradipta, Adya Rizky; Irunsah, Aslan (Indonesian Scholar Society, 2022)
The use of TiO2 nanocomposite modified with Fe3O4 dan Ni dopping for silver ion photoreduction has been successfully carried out. In this study, nanocomposites were fabricated through the sol-gel technique. Structure, optical, and magnetic properties were analyzed using XRD, DRUV-Vis, FTIR, and VSM analysis. The XRD pattern revealed the anatase phase of TiO2 and the iron oxide formed was Fe3O4. UV-Vis spectroscopy showed the formation of absorption in the visible region in the presence of Ni doping. The nanocomposite had magnetic properties of 12.6 emu/g with paramagnetic type. TiO2 nanoparticles presented the percentage reduction of Ag ions with UV and Visible light of 82.65% and 21.43%, respectively, while Fe3O4/ TiO2-Ni with UV and Visible light were 80.93% and 90.72%, respectively. Ni-dopped nanocomposites had shown high photocatalytic activity under both UV and Visible irradiation.